Little man, little man : a story of childhood - Baldwin, James, 1924-1987 (Duke University Press, 2018)
Four-year-old TJ spends his days on his lively Harlem block playing with his best friends WT and Blinky and running errands for neighbors. As he comes of age as a "Little Man" with big dreams, TJ faces a world of grown-up adventures and realities. Baldwin's only children's book celebrates and explores the challenges and joys of black childhood. This new edition includes a foreword by Baldwin's nephew Tejan "TJ" Karefa-Smart and an afterword by his niece Aisha Karefa-Smart, with an introduction by two Baldwin scholars. In it we not only see life in 1970s Harlem from a black child's perspective, but we also gain a fuller appreciation of the genius of one of America's greatest writers.